2014
DOI: 10.1002/syn.21762
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y-stimulated [35S]GTPγs functional binding is reduced in the hippocampus after kainate-induced seizures in mice

Abstract: Kainate-induced seizures constitute a model of temporal lobe epilepsy where prominent changes are observed in the hippocampal neuropeptide Y (NPY) system. However, little is known about the functional state and signal transduction of the NPY receptor population resulting from kainate exposure. Thus, in this study, we explored functional NPY receptor activity in the mouse hippocampus and neocortex after kainate-induced seizures using NPY-stimulated [(35) S]GTPγS binding. Moreover, we also studied levels of [(12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…NPY receptor autoradiography was carried out as previously described (Woldbye et al, 2005, Elbrønd-Bek et al, 2014. Procedures were performed at RT if not stated otherwise.…”
Section: Npy Binding Autoradiographymentioning
confidence: 99%
“…NPY receptor autoradiography was carried out as previously described (Woldbye et al, 2005, Elbrønd-Bek et al, 2014. Procedures were performed at RT if not stated otherwise.…”
Section: Npy Binding Autoradiographymentioning
confidence: 99%
“…27 Here, we addressed the activity of NPY receptors using the [ 35 S]GTPγS binding assay in retinal slices. Other studies have reported alterations in the NPY system at specific time points, under different experimental condition and in other tissues, 45,46 highlighting that the NPY system is fairly dynamic and changes might only be detectable temporarily. However, it should be noted that by stimulating [ 35 S]GTPγS binding with NPY, we assessed the simultaneous activation of all NPY receptors.…”
Section: Discussionmentioning
confidence: 92%
“…Here, we used an experimental paradigm of 4 weeks of DM and/or 2 weeks of sitagliptin treatment. Other studies have reported alterations in the NPY system at specific time points, under different experimental condition and in other tissues, 45,46 highlighting that the NPY system is fairly dynamic and changes might only be detectable temporarily. Taken together, the findings from our study demonstrate that after 4 weeks of DM, NPY mRNA and protein levels decrease in diabetic retina.…”
Section: Discussionmentioning
confidence: 92%
“…Treatment with NPY has been shown to have therapeutic effects for both kainate-and trimethyltin-induced seizure models of temporal lobe epilepsy (43,44). The major protective effect of NPY in these models is thought to be through direct stimulation of neurons.…”
Section: Discussionmentioning
confidence: 99%